Islamic Financial Analysis: A Review of Halal Investment Practices in the Capital Market - Naufal, Muhammad Naufal; Abiy, Hamanda Abiy'yu (Cattleya Darmaya Fortuna, 2024)
This study analyzes the performance of Islamic sukuk in the Indonesian capital market with a focus on price changes and yields of several existing sukuk instruments. The data used includes daily price changes and annual yields of various Islamic sukuk, including Sukuk Negara Series 001, Sukuk Tabungan Indonesia, and Sukuk Corporate X. The results show that all sukuk analyzed experienced positive price increases, with Sukuk Negara Series 001 recording the largest price increase of 5%. On the other hand, Sukuk Corporate X offers the highest yield of 7%, attractive to investors seeking higher returns. Despite variations in yields and price changes, the Islamic sukuk market in Indonesia shows positive potential to continue to grow. This study provides important insights into Islamic investment options that can be used as a reference by investors to choose sukuk instruments that suit their investment goals.